DISPARITY OF DECISIONS OF CRIMINAL ACTIONS OF CORRUPTION PERFORMED BY HEAD OF POLITICAL PARTY - Hartanto Hartanto (Faculty of Law-Universitas Bandar Lampung, 2022)
Corruption is a big problem and is suspected to be a contributor to the increase in poverty in Indonesia, this corruption crime does not recognize any position or background. The author sees that corruption is a legal domain that is often influenced by the political field, although what should be considered is the domain of sociology/legal sociology. The general chairman of the party, in this case, the former, who was supposed to have helped build the country when he was in power, did not seem to meet the expectations of the people, because when he was in power he actually did corruption. Corruption in the circle of political parties is very influential on public confidence in political parties that are the driving force of democracy. Political phenomena that affect the law in the form of judges' decisions / verdicts will increase the disparity of decisions. Starting from the decision related to Romy, it is compared with the decision of Anas U, Suryadharma A, Luthfi H I. How our law looks, really depends on the